1998
DOI: 10.1016/s0022-2275(20)33865-7
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of eicosapentaenoic acid to chain-shortened omega–3 fatty acid metabolites by peroxisomal oxidation

Abstract: Human skin fibroblasts can convert arachidonic acid to 14-and 16-carbon polyunsaturated fatty acid products by peroxisomal ␤ -oxidation. The purpose of this study was to determine whether similar products are formed from eicosapentaenoic acid (EPA) and whether EPA and arachidonic acid compete for utilization by this oxidative pathway. Three radiolabeled metabolites with shorter retention times than EPA on reverse-phase high-performance liquid chromatography accumulated in the medium during incubation of fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Together, this suggests that the increased production of the PIFAs is due to an increase in the availability of the substrates. Thus far, 16:4(n-3) has only been described to be formed via peroxisomal oxidation from EPA (Williard et al, 1998). Given our results, it is likely that similar to KHT, 16:4(n-3) functions downstream of the COX-TXAS pathway.…”
Section: Msc-induced Resistance Is Prevented By Intervening With the Cyclooxygenase (Cox)-1/thromboxane Synthase (Txas) Pathwaymentioning
confidence: 56%
“…Together, this suggests that the increased production of the PIFAs is due to an increase in the availability of the substrates. Thus far, 16:4(n-3) has only been described to be formed via peroxisomal oxidation from EPA (Williard et al, 1998). Given our results, it is likely that similar to KHT, 16:4(n-3) functions downstream of the COX-TXAS pathway.…”
Section: Msc-induced Resistance Is Prevented By Intervening With the Cyclooxygenase (Cox)-1/thromboxane Synthase (Txas) Pathwaymentioning
confidence: 56%
“…Williard et al . found that EPA can be converted to 16:4( n ‐3) by peroxisomal oxidation 42 . Because of limited sample of mouse blood plasma, we were unable to determine PIFA levels in this study.…”
Section: Discussionmentioning
confidence: 87%
“…The most abundant epoxy-fatty acid metabolites of 11,12-and 14,15-EET produced by the fibroblasts contained 16-carbons. Likewise, 16-carbon metabolites are the most abundant products that accumulate in the medium during the ␤-oxidation of 12-, and 15-hydroxyeicosatetraenoic acids (27,33), 11,12-DHET (27), arachidonic acid (29), and eicosapentaenoic acid (34). The 16-carbon products formed from each of these compounds contain…”
Section: Discussionmentioning
confidence: 99%
“…The lipids extracted from the medium and the hydrolyzed cell lipids were converted to pentafluorobenzyl (PFB) esters by incubation for 20 min at room temperature with 5 L PFB bromide in 10 L N,N-diisopropylethylamine and 50 L methylene chloride as described previously (34). The products were separated with a Hewlett-Packard 5890A gas-liquid chromatograph containing a 15 m ϫ 0.32 mm column coated with 0.1 m DB-1 ( J. W. Scientific, Rancho Cordova, CA) at a 2 mL/min helium flow rate.…”
Section: Identification Of Eet Metabolitesmentioning
confidence: 99%